Process Simulating of Heat Transfer in High-temperature Thermocouples; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Atroshenko Yu. K. Yuliana Konstantinovna (2015, 2015)
Title screen